Clinical profile and predictors of outcome of patients with diphtheria in tertiary care pediatric centre from Southern India - H. S., Vinayaka; D., Manoj; G. V., Basavaraj (International Journal of Contemporary Pediatrics, 2018)
Background: Diphtheria is still a fatal infectious disease even in this era of universal immunization. The disease has been completely eradicated in most of the developed countries. On the contrary, in developing countries, although the incidence has drastically declined, still account for 80-90% of global burden. The objectives of this study is to study the clinical profile and predictors of outcome of patients with diphtheria. Methods: All children between the age group of 0 to 15 years admitted with signs and symptoms of diphtheria during January to August 2017 formed the study group. Throat swab for Albert’s stain and culture sensitivity were sent in all patients at the time of admission. All children were started on parenteral crystalline penicillin and Anti Diphtheritic Serum as recommended. All details that is demographic data, clinical features, immunization status, complications and outcome were entered in a proforma and analysed. Several variables were compared among the survivors and non-survivors to determine the predictors of outcome. Outcome is defined as either recovered or died. Results: A total of 42 patients were included in the study group. Among 42 patients, 21 (50 %) were between 5-10 years, 12 (28 %) were between 0-5 years and 9 patients (22 %) were more than 10 years. Most common symptoms were fever followed by throat pain, difficulty in swallowing and bull neck. Alberts stain was positive in 83% of cases and culture positivity in 30% of cases. Myocarditis (47%) was the most common complication followed by acute kidney injury (40%), airway compromise (59%) and thrombocytopenia (42%). A total number of 19 patients died. Conclusions: Diphtheria is highly fatal disease with increased mortality. Myocarditis was the commonest and most serious complication. Presence of myocarditis, AKI, thrombocytopenia, airway compromise and inadequate immunization are important predictors of outcome.